The Big Nine : how the tech titans and their thinking machines could warp humanity - Webb, Amy, 1974- (PublicAffairs, 2019)
"A call-to-arms about the broken nature of artificial intelligence, and the powerful corporations that are turning the human-machine relationship on its head. The big nine corporations (Amazon, Google, Facebook, Tencent, Baidu, Alibaba, Microsoft, IBM and Apple) may be inadvertently building and enabling vast arrays of intelligent systems that don't share our motivations, desires, or hopes for the future of humanity."--Provided by publisher.